2020
DOI: 10.1002/jgm.3271
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of lncRNAs in breast cancer: Meta‐analysis shows no association with susceptibility

Abstract: Background: Long non-coding RNAs (lncRNAs) have been the target of considerable attention for their roles in many biological processes. Only a small portion of lncRNAs are functionally characterized, and several approaches have been proposed for investigating the roles of these molecules, including how polymorphisms in lncRNA genomic sites may interfere with their function. Allele frequency variation in single nucleotide polymorphisms (SNPs), for example, has been associated with several diseases, including br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
1
5
1
Order By: Relevance
“…Our data were similar to what conducted by [19] who found that the frequency of T allele was significantly higher in breast cancer patients compared to the controls (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Our data were similar to what conducted by [19] who found that the frequency of T allele was significantly higher in breast cancer patients compared to the controls (P < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…This study also demonstrated that TGAC, CTAT, and TTAT polymorphisms substantially lower the BC risk. In contrast, Mathias et al [ 89 ] predicted no correlation between BC susceptibility and rs4759314, rs920778, rs12826786, and rs1899663 in HOTAIR.…”
Section: The Role Of Hotair In Breast Cancer Managementmentioning
confidence: 97%
“…They can affect various aspects of cell activities, such as growth and proliferation, survival, migration and invasion, as well as genomic stability. Thus it is increasingly evidenced that lncRNAs play a key role in tumor growth, lymph node/distant metastasis, and patient survival [22], and the single nucleotide polymorphisms (SNP) of lncRNAs are identified as risk factors and correlated to tumorigenesis and metastasis of cancers [34,35]. More interestingly, some lncRNAs are found to be increased in the plasma of cancer patients, yielding the possibility as diagnostic markers in blood [36,37].…”
Section: Lncrna Biology and Functionmentioning
confidence: 99%